Expression of antigen gp5 of prrs virus in tobaco - Sen, Dao Thi; Ha, Chu Hoang; Van, Nguyen Tuong (Academia Journal of Biology, 2018)
PRRS (Porcine reproductive and respiratory syndrome) is the most significant infectious disease currently devastating the swine industry. In order to diversify antigen sources for vaccine production to against PRRSV, co-expressing LTB and PRRSV GP5- an important structure protein GP5 of PRRSV were expressed in tobacco. Genes encoded for GP5 of PRRSV isolated from pigs infected PRRSV in Vietnam in 2010 and was constructed in plant expression vector under the control of seed specific phaseolin promoter and constitutive promoter 35S. The genes were then transferred into the C9-1 tobacco using Agrobacterium. The stable insertion of LTB-GP5genes in genomeoftransgenic tobacco was confirmed by PCR and RT-PCR. Western hybridization indicated that fused protein LTB-GP5 was successful expressed in tobacco seeds. Analysis of transgenic tobaco seeds revealed that under regulation of promoter beta-phaseolin, the level expression of GP5 was significant improved as quantiﬁed by ELISA (2.2 % of total soluble protein). This preliminary result is a foundation for expression of GP5 in seeds of other plants in the future.